Pernikahan Beda Agama dalam Konteks Multikultural: Kajian Hukum Islam Berdasarkan Kaidah-Kaidah Qawaid Fiqhiyyah Al-Ammah - Nur Najwa; Dina Safitri; Ahmad Arif Setiawan; Lisnawati Lisnawati (STIKes Ibnu Sina Ajibarang, 2025)
This study examines the application of Qawaid al-Fiqhiyyah al-Ammah in the legal framework of interfaith marriage within Indonesia’s multicultural society, characterized by religious and cultural diversity. The research background highlights the challenge of aligning sharia principles with the social dynamics of a multicultural context, particularly concerning the potential harm of interfaith marriages. The objective is to understand how fiqh principles, such as Ad-Dhararu Yuzal and Kullu Syarthin Mukhaalif Li Ushul al-Syari’ah Fa Huwa Baathil, serve as methodological tools to evaluate the law of interfaith marriage. A qualitative approach is employed, utilizing normative-juridical and descriptive-analytical methods. The normative-juridical analysis involves studying the Qur’an (Surah Al-Baqarah: 221 and Al-Maidah: 5) and fiqh principles, while the descriptive-analytical approach explores the perspectives of fiqh schools (Hanafi, Maliki, Shafi’i, Hanbali) and Indonesia’s social realities. Data were collected through a literature review, including classical fiqh texts, academic journals, and contemporary Islamic legal documents, analyzed deductively and inductively. The study provides a comprehensive understanding of the flexibility of fiqh principles in addressing interfaith marriage challenges while upholding sharia and minimizing social harm.